2022
DOI: 10.3390/vetsci9120705
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant Escherichia coli Strains Isolated from Captive Giant Pandas: A Reservoir of Antibiotic Resistance Genes and Virulence-Associated Genes

Abstract: Recent studies showed that Escherichia coli (E. coli) strains isolated from captive giant pandas have serious resistance to antibiotics and carry various antibiotic resistance genes (ARGs). ARGs or virulence-associated genes (VAGs) carried by antibiotic-resistant E. coli are considered as a potential health threat to giant pandas, humans, other animals and the environment. In this study, we screened ARGs and VAGs in 84 antibiotic-resistant E. coli strains isolated from clinically healthy captive giant pandas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 66 publications
0
5
3
Order By: Relevance
“…coli from pet dogs. According to previous study, phylogenetic grouping is closely related to virulence genes (group A and B1 strains carry fewer virulence genes, while group B2 and D strains carry more virulence genes) [ 6 ], whereas in our present study, no significant difference was observed in the average number of VAGs carried by per strains between commensal groups and virulent extraintestinal-related groups. These phenomena suggest that antimicrobial resistance may increase the possibility of carrying more virulent factors (for example, the number of VAGs carried) in E .…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…coli from pet dogs. According to previous study, phylogenetic grouping is closely related to virulence genes (group A and B1 strains carry fewer virulence genes, while group B2 and D strains carry more virulence genes) [ 6 ], whereas in our present study, no significant difference was observed in the average number of VAGs carried by per strains between commensal groups and virulent extraintestinal-related groups. These phenomena suggest that antimicrobial resistance may increase the possibility of carrying more virulent factors (for example, the number of VAGs carried) in E .…”
Section: Discussioncontrasting
confidence: 53%
“…Recent studies have shown that there was an association between ARGs and VAGs, and have proposed that they were linked and interacted with each other [6,56]. In order to explore the virulence traits and the association of ARGs and VAGs in MDR E. coli, we analyzed the distribution of VAGs in MDR strains.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, overuse of antibiotics can enhance the prevalence of drug resistance genes, resulting in poorer treatment outcomes. Antibiotic-Resistant Escherichia coli and multidrug-resistant Klebsiella pneumoniae and Raoultella have been screened from the intestinal microbiota of giant pandas (Fan et al, 2022;Shahi et al, 2023). Therefore, it is particularly important to find a more effective way to treat intestinal diseases.…”
Section: Introductionmentioning
confidence: 99%